2024
DOI: 10.1097/upj.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

US Clinical Practice Patterns of Intravesical Chemotherapy for Bacillus Calmette-Guérin–Unresponsive and Bacillus Calmette-Guérin–Exposed Nonmuscle-Invasive Bladder Cancer

Mohamad Abou Chakra,
Neal D. Shore,
Rachelle Dillon
et al.

Abstract: Introduction:The goal of this survey was to evaluate the treatment and practice pattern of patients with high-grade papillary Ta, T1 nonmuscle-invasive bladder cancer (NMIBC), and carcinoma in situ (CIS) in bacillus Calmette-Guérin (BCG)eunresponsive (with adequate BCG exposure ¼ adequate BCG) and those with less than adequate BCG exposure (BCG-exposed).Methods: An internet-based survey with a target duration of 5 minutes was sent to US urologists who manage patients with NMIBC. Respondents were recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In a survey conducted among urologic oncologists attending the 2022 Society of Urologic Oncology meeting, roughly 70% reported using Gem/Doce as their preferred agent for BCG-unresponsive cases. 4 In contrast, only 10% of mostly community-based urologists in the current survey reported using Gem/Doce. The source of this discrepancy may well be multifactorial but unfamiliarity with Gem/Doce and its advantages over single agents likely played a role, as well as logistical issues of increased treatment time imposed by sequenced Gem/Doce.…”
mentioning
confidence: 62%
“…In a survey conducted among urologic oncologists attending the 2022 Society of Urologic Oncology meeting, roughly 70% reported using Gem/Doce as their preferred agent for BCG-unresponsive cases. 4 In contrast, only 10% of mostly community-based urologists in the current survey reported using Gem/Doce. The source of this discrepancy may well be multifactorial but unfamiliarity with Gem/Doce and its advantages over single agents likely played a role, as well as logistical issues of increased treatment time imposed by sequenced Gem/Doce.…”
mentioning
confidence: 62%
“…A study of United States practice patterns showed that only 25% of surveyed urologists would consider radical cystectomy for BCG-unresponsive high-grade papillary disease. Meanwhile, more than half regularly utilized intravesical chemotherapy for these patients [58]. This has spurred the use of novel combinations of existing intravesical therapies, intravesical gene therapies, intravenous immunotherapy, and novel methods of drug delivery in BCG-unresponsive NMIBC.…”
Section: Bcg-unresponsivementioning
confidence: 99%
“…2 In another survey administered to Arab urologists on the same topic, 30% of respondents were using intravesical chemotherapy for these patients, while only 12% were using SDCs. 3 Data from Europe showed that 50% of urologists may use intravesical chemotherapy (most commonly mitomycin C) for BCG failure. 4 The reason for the disparity in the treatment plan could be complex, but practical concerns arising from the logistical requirements to establish an SDC clinic also probably had an impact, as did the lack of knowledge about SDC and its benefits.…”
Section: Reply By Authorsmentioning
confidence: 99%